Chemical Composition and Spectroscopic Characteristics of Heat-Treated Rubies from Madagascar, Mozambique and Tanzania - Ling Yang; Qi Lu; Di Ma; Hairong Zheng; Ruoshui Hu; Zhuohang Shi; Binrong Qin (Crystals, 2023)
The chemical composition and spectra of rubies heat-treated with high temperatures (above 1200 °C) from Madagascar, Mozambique and Tanzania were analyzed by electron microprobe, LA-ICP-MS, Fourier transform infrared spectroscopy, Raman spectroscopy and UV-VIS spectroscopy. Compared with untreated rubies, the red hue of treated ruby intensifies while its blue tint diminishes, leading to increased cracks. The infrared spectra exhibit a distinct absorption peak at 3738 cm−1, attributed to water because of thermal treatment. After heat treatment, the absorption intensity decreases. Ultraviolet radiation reveals an enhancement in the electron transition of Cr3+ and ion transition of Fe3+ and Fe2+, with a shift towards shorter wavelengths observed in the absorption bandwidth. These can be utilized to indicate the basis of ruby identification through heat treatment.